Complement factor D as a predictor of Achilles tendon healing and long‐term patient outcomes. Issue 6 (21st May 2022) - Chen, Junyu; Wang, Jin; Hart, David A.; Ahmed, Aisha S.; Ackermann, Paul W.
Abstract: Dense connective tissue healing, such as tendon, is protracted leading to highly variable and unsatisfactory patient outcomes. Biomarkers prognostic of long‐term clinical outcomes is, however, unknown. The present study was designed to investigate the proteomic profile of healing, identify potential biomarkers, and assess their association with the patient's long‐term outcomes after ATR. Quantitative mass spectrometry analysis demonstrated 1423 proteins in healing and contralateral healthy Achilles tendons of 28 ATR patients. Comparing healing at 2 weeks and healthy protein profiles, we identified 821 overlapping, 390 upregulated, and 17 downregulated proteins. Upregulated proteins are related mainly to extracellular matrix organization and metabolism, while downregulated pathways were associated with exocytosis in immune modulation and thrombosis formation. Further proteomic profiling in relation to validated patient outcomes revealed the downregulated pro‐inflammatory complement factor D (CFD) as the most reliable predictive biomarker of successful tendon healing. Our finding showed a comprehensive proteomic landscape and bioinformatics on human connective tissue, indicating subtype‐specific and shared biological processes and proteins in healing and healthy Achilles tendons, as well as in tendons related to good and poor patient outcomes. Inflammatory protein CFD and serpin family B member 1 were finally identified as potential predictive biomarkers of effective healing outcomes when combined the proteomic profiles with a validated clinical database. Following the future elucidation of the mechanisms associated with the identified biomarkers as predictors of good outcomes, our findings could lead to improved prognostic accuracy and development of targeted treatments, thus improving the long‐term healing outcomes for all patients.